A feasibility study of internal and external based system for pipeline leak detection in upstream petroleum industry - Sulaima, Mohamad Fani; Faizal, Abdullah; Jali, Mohd Hafiz; Wan Daud, Wan Mohd Bukhari; Mohd Nasir, Mohamad Na'im; Baharom, Mohamad Faizal (American-Eurasian Network for Scientific Information, 2014)
Offshore underwater pipelines leaks begin at poor joints, corrosions and cracks and slowly progress to a major leakage. Accidents, terror, sabotage, or theft are some of human factor of pipeline leak. The primary purpose of Pipeline Leak Detection Systems(PLDS) is to assist pipeline managers in detecting and locating leaks earlier. PLDS provides an alarm and display other related data to the pipeline engineers for their decision-making. It is also beneficial because of PLDS can enhance their productivity by reduced downtime and inspection time. PLDS can be divided into internally base PLDS and external hardware base PLDS. The purpose of this paper is to study the various types of leak detection systems based on internal and externally system simultaneously.Meanwhile to define a set of key criteria for evaluating the characteristics of this system and provide an evaluation method of leak detection technology as a guideline of choosing the appropriate system in the future.